Enhancing Emotional Intelligence Through Narrative Pedagogy: Lessons from the Panchatantra - Porwal, Surbhi (Journal of Research in Vocational Education, 2026)
The Panchatantra, an ancient collection of Indian fables, has been a cornerstone of moral and ethical education for centuries. Each story is rich with lessons on human behavior, relationships, and emotional management. Emotional intelligence (EI), which involves the ability to understand, manage, and use emotions effectively, is crucial in fostering personal and social development. This paper explores how the stories of the Panchatantra can be used as tools to enhance emotional intelligence in individuals, especially children, by imparting essential life skills such as empathy, self-awareness, emotional regulation, and social harmony.